Tree replanter: a solar powered approach - V, Aromal; G.L, Gokulnath; Prasad, Geena (International Journal of Engineering and Technology, 2018)
Tree Transplantation is referred to as the procedure of unearthing the trees and replanting them from one location to another with the objective of re-growing the tree to a new location. This involves moving the tree with the root ball-system thereby protecting while tak-ing up the wider roots. In the proposed design, we use electromagnetic linear actuators working with solar energy instead of hydraulic or pneumatic actuators which consume fossil fuels. Here, a three-blade system is used to unearth the tree wherein the rare blades are opened to encircle the tree and the blades are positioned around the tree to ensure that the root ball is at an equal distance from all sides of the trunk. The blades are closed to remove the tree with the root ball intact. The tree with the spade is adjusted to the truck for safe transport.Â